2006
DOI: 10.1002/dvdy.20967
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of a stem cell niche: The case of the Drosophila ovary

Abstract: In this work, we demonstrate a powerful new tool for the manipulation of the stromal component of a wellestablished Drosophila stem cell niche. We have generated a bric-a-brac 1 (bab1)-Gal4 line that drives UAS expression in many somatic ovary cell types from early larval stages. Using this Gal4 line, we could effectively induce FLP/FRT-mediated recombination in the stromal cells of the ovarian germline stem cell niche. Mutant clones were observed in the developing ovary of larvae and pupae, including in somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 58 publications
3
87
2
2
Order By: Relevance
“…In terminal filament and cap cells, for example, weak expression of growth factors may be achieved using boi-Gal4 or sgg-Gal4 without having dramatic effects on the development of the fly (Figure 2). bab-Gal4 remains the most robust driver for terminal filament and cap cells, with many examples of its successful use for reducing gene expressing with RNAi (Bolívar et al 2006;Hartman et al 2010Hartman et al , 2013Sahai-Hernandez and Nystul 2013;Xin et al 2013). All the Gal4 lines we identified that promoted expression in IGS cells also exhibited expression in other cell types, including cap cells, FSCs, and/or pre-follicle cells.…”
Section: Discussionmentioning
confidence: 98%
“…In terminal filament and cap cells, for example, weak expression of growth factors may be achieved using boi-Gal4 or sgg-Gal4 without having dramatic effects on the development of the fly (Figure 2). bab-Gal4 remains the most robust driver for terminal filament and cap cells, with many examples of its successful use for reducing gene expressing with RNAi (Bolívar et al 2006;Hartman et al 2010Hartman et al , 2013Sahai-Hernandez and Nystul 2013;Xin et al 2013). All the Gal4 lines we identified that promoted expression in IGS cells also exhibited expression in other cell types, including cap cells, FSCs, and/or pre-follicle cells.…”
Section: Discussionmentioning
confidence: 98%
“…Expression of this construct under the control of the engrailed or bab1 promoter (Bolivar et al, 2006) led to encapsulation defects and abnormal stalk morphology (Fig. 2K-M).…”
Section: Pigs Is Essential For Developmentmentioning
confidence: 99%
“…Cap cell differentiation occurs in early pupae as TF formation is completed. The niche develops by cell rearrangement and cell recruitment, so that an individual niche is polyclonal in origin, technically limiting the ability to perform genetic loss-of-function studies in the niche (68,69). Advances in available genetic tools, such as the recent development of a method to target clone formation to the somatic gonadal cells (69), hold promise to expand the genetic analysis of niche morphogenesis and GSC maintenance.…”
Section: Female Gsc Niche Developmentmentioning
confidence: 99%